Kehancuran dan Harapan Baru: Gempa, Tsunami dan Likuifaksi di Palu Sulawesi Tengah 2018 - Amiruddin Amiruddin; Yulfa Lumbaa (Institut Nalanda, 2024)
Natural disasters are events that require significant attention, and it is imperative to protect nature and remain submissive to the Creator. The purpose of this research is to express the author's concern regarding the tragedy that occurred in the city of Palu, Central Sulawesi, on September 28, 2018. In this study, the researcher employed a literature review method, sourcing references from journals, books, and information related to the Palu tragedy at that time. The findings of this research indicate that on September 28, 2018, at 18:42 WITA, a natural disaster occurred in the form of a 7.4 magnitude earthquake, followed by a tsunami and liquefaction. This was triggered by underwater sediment landslides. Mythical aspects related to this tragedy are issues that have not been scientifically validated. The Nomoni Festival, which includes the Balia Dance, is considered by some community members to be contrary to their religious beliefs. Some people believe that such practices invite divine wrath, manifesting as natural disasters. However, scientific explanations for the disaster indicate that the earthquake and tsunami were the result of tectonic activity, which can be geologically explained. It is essential to combine scientific understanding with respect for local beliefs to enhance disaster preparedness and mitigation in the future. This research aims not only to reveal the scientific facts behind the Palu tragedy but also to raise awareness about the importance of maintaining ecological balance and gaining a deeper understanding of natural phenomena.